PRIVACY POLICY AND PERSONAL DATA PROTECTION ON THE INTERNET: A CASE STUDY OF TURKEY - Lazović, Danica (Political Review, 2023)
The right to privacy and the protection of personal data are two highly related and intertwined rights. In the era of globalization, the ever more extensive and widespread use of communication technologies, the challenge of protecting these rights from abuse in non-democratic states arises. The analysis of the legislation of the Republic of Turkey shows that Turkish state has formally regulated the area of protection of the right to privacy and protection of personal data on the Internet, while practice shows many abuses and violations. The development of the Internet and other means of communication has enabled the authoritarian and undemocratic regime to collect personal data, use it for the purpose of dealing with political dissidents and consequently violate the general principles of the rule of law. The political changes that followed the referendum held in 2017. significantly contributed to the growth of the president’s power. These constitutional changes resulted in a change in the share of power in the decision-making process regarding the selection of members of the National Data Protection Authority. In this sense, the Council of Ministers was completely squeezed out of the membership selection process, and the influence of the president was doubled. Referring to the existing legislation, the state, under the guise of protecting national interests and national security, violated the right to privacy and the right to protect personal data. The same excuse was used for the purpose of arresting political dissidents and unfit journalists, which generally led to a large reduction of the rule of law in this country. The main results and conclusions arising from this article refer to the recognition of the trend of general reduction and violation of the right to privacy and protection of personal data, which is connected and explained by constitutional changes and implementation of the adopted legislation.